The essence of digital assets: conceptual foundations and contemporary context - Budnyk, Volodymyr (Herald of Economics, 2025)
Introduction. Digital assets, such as cryptocurrency, tokens and NFTs (non-fungible tokens), other digital objects are rapidly changing the economic landscape, creating new opportunities for businesses and investors. However, unresolved issues regarding their legal regulation and accounting pose serious challenges for governments, businesses and financial institutions. This problem is of particular importance as digital assets become increasingly important in the global economy. Purpose of the study. The purpose of the study is to analyze the content of digital assets in a global context, to consider their specifics and place in modern economic realities. Special attention is paid to the challenges that arise in connection with unresolved issues regarding the regulation of digital assets. Research methods. In the process of research and writing the article, the following methods were used: dialectical, systems analysis, generalization, comparison, logical. Results. The article explores the essence of digital assets as an innovative object, it is determined that despite the similarity, the terms «digital assets» and «virtual assets» have different emphases in application, understanding their differences allows us to more accurately determine the legal status of the asset, the scope of its use and the features of accounting or regulation; digital assets cover a wider range of objects, while virtual assets are a subcategory of digital assets focused on the financial sphere. The main challenges associated with the use of digital assets in the financial and economic spheres are also highlighted. Among them are regulatory uncertainty, volatility risks, security issues and the lack of uniform accounting and financial reporting standards. The author emphasizes that the development of digital assets requires a clear legal framework and the implementation of international standards. The author predicts the growing role of digital assets in financial transactions, investments and tokenization of traditional assets. The conclusions emphasize that digital assets are not only a technological but also an economic phenomenon that transforms traditional approaches to storing and managing values. Prospects. Further study of the study of digital assets will not only allow for a deeper understanding of their nature, but will also contribute to the development of effective approaches to their regulation, integration into traditional economic processes and maximization of their potential in the modern world. The need to create unified approaches to the classification, assessment and reflection of digital assets in financial reporting is urgent. Research may include the development of new accounting standards that take into account the specifics of cryptocurrencies, tokens and NFTs.